Development of ionic-complex-based nanostructured lipid carriers to improve the pharmacokinetic profiles of breviscapine - Li Mei; Zheng Yong; Shan Feng-ying; Zhou Jing; Gong Tao; Zhang Zhi-rong (Acta Pharmacologica Sinica, 2016)
Aim: Breviscapine isolated from the Chinese herb Erigeron breviscapus (Vant) Hand-Mazz is widely used to treat cardiovascular and cerebrovascular diseases. The aim of this study was to improve the pharmacokinetic profiles of breviscapine using nanostructured lipid carrier based on an ionic complex formation. Methods: Breviscapine nanostructured lipid carrier (Bre-NLC) was prepared using the thin film homogenization method. The morphology of Bre-NLCs was determined using transmission electron microscopy. The mean particle size, polydispersity index, zeta-potential analysis and entrapment efficiency were analized. In vitro release was studied using the dialysis method. In vitro stability was studied in fresh plasma and liver slurry of rats. In vivo pharmacokinetics was analyzed in rats after intravenous injection of a dose equivalent to breviscapine (10 mg/kg). Results: The Bre-NLCs were spherical with a mean particle size of ~170 nm, a zeta potential of ~20 mV and a high entrapment efficiency of ~89%. Compared with a commercially available solution, a substantial decrease in the cumulative release of breviscapine was found for the Bre-NLCs. The NLC has a significantly protective effect against the liver enzyme degradation of breviscapine. After intravenous administration in rats, the Bre-NLCs exhibited a 32 times increase in the AUC0–t and a 12 times increase in T1/2 as compared to the commercially available breviscapine solution. Conclusion: The results demonstrate that the NLC has great potential to use as a novel sustained release system for breviscapine.